Babesia spp. infection in dogs from rural areas of São Paulo State, Brazil - O'Dwyer, Lucia Helena [UNESP]; Lopes, Viviane Von Ah [UNESP]; Rubini, Adriano Stefani [UNESP]; Paduan, Karina Dos Santos [UNESP]; Martins Ribolla, Paulo Eduardo [UNESP] (Brazilian Coll Veterinary Parasitology, 2009)
The status of Babesia spp. infection in dogs from rural areas of São Paulo State, Brazil was Studied. For this, l 50 animals were examined by blood smears and by PCR; the presence of tick infestation was also investigated. By the blood smear examination, 3 animals (2%) were detected positive and by PCR for Babesia spp. 12 (8%) were positive, with bands Visualized in 450 bp. Rhipicephalus sanguineus or Amblyomma spp. were found on 36 (24%) of the 150 dogs. Amblyomma species found were A. cajennense (9/36-25%) and A. ovale (9/36-25%). It was not possible to correlate the presence of R. sanguineus and the infection with Babesia spp. The sequencing of four positive samples demonstrated close identity with B. canis vogeli already characterized in Brazil.

A presença de infecção por Babesia spp. em cães de áreas rurais do Estado de São Paulo, Brasil foi investigada. Para tanto, 150 cães foram examinados por técnicas parasitológicas de esfregaços sanguíneos e moleculares (PCR), e também, foi verificada a presença de carrapatos nestes animais. Pela análise de esfregaços sanguíneos, 3 (2%) dos cães estavam infectados, enquanto pela PCR, 12 (8%) dos animais foram positivos com bandas aproximadas de 450 pares de base (pb). Foram observados 36 (24%) cães infestados com Rhipicephalus sanguineus ou com Amblyomma spp. As espécies de Amblyomma observadas foram A. cajennense (25%) e A. ovale (25%). Não foi possível correlacionar a presença de R. sanguineus com a infecção por Babesia spp. O seqüenciamento de quatro amostras positivas demonstrou alta identidade com B. canis vogeli, já caracterizada no Brasil.
Infecção por Babesia spp. em cães de áreas rurais do estado de São Paulo, Brasil
Keywords: Babesia canis vogeli; dogs; rural areas; blood smears; PCR